Prognosis of limited resection versus lobectomy in elderly patients with invasive lung adenocarcinoma with tumor size less than or equal to 2 cm - Chen, Tianxiang (J Thorac Dis, 2018)
BACKGROUND: This study aimed to evaluate the prognostic difference between limited resection and lobectomy among elderly patients with small size lung adenocarcinoma. METHODS: A total of 666 patients >65 years old with stage I lung adenocarcinoma and tumor size ≤2 cm were included. The patient survival was evaluated by disease-free survival (DFS) and overall survival (OS). Results: No DFS or OS advantage was found between the lobectomy and wedge resection groups when tumor sizes were ≤1 cm (DFS, P=0.112; OS, P=0.294). The wedge resection group had a significantly worse OS (P=0.041) than that in the lobectomy group when tumor sizes were >1 cm and ≤2 cm. CONCLUSIONS: We conclude that wedge resection may be a reasonable surgical choice for elderly patients with tumor sizes ≤1 cm.